MAGICAL REALISM AND ITS EFFECTS ON THE CHARACTERS IN THE MOVIE SORRY TO BOTHER YOU - Shanda, Billy Febriand; Anggraeni, Diana; Fernanda, Andri (Argopuro: Jurnal Multidisiplin Ilmu Bahasa, 2025)
This study focused on Magical Realism and aimed to identify the elements of magical realism presented in the movie Sorry to Bother You by Boots Riley. It specifically concentrated on revealing the five key elements of magical realism using Wendy B. Faris' theory. The data was analysed through a descriptive qualitative method, and note-taking was used to collect relevant information. The results showed that the elements of magical realism are clearly narrated in the movie, influencing the characters. This was demonstrated by the presence of all five magical realism elements: Irreducible Elements, Phenomenal World, Unsettling Doubt, Merging Realms, and Disruption of Time, Space, and Identity. This study also examined the levels of magical realism in the movie, confirming the strong presence of both magical and realistic aspects. This is evidenced in the movie's narrative, filled with Wendy B. Faris' magical realism characteristics, illustrating magical events in a modern setting. Moreover, Sorry to Bother You movie by Boots Riley is identified as a magical realism work due to the fulfillment of these elements and the strong balance between magic and realism.